Theoretical framework for confined ion transport in two-dimensional nanochannels - Shouwei Liao; Yanchang Liu; Libo Li; Li Ding; Yanying Wei; Haihui Wang (Nature Communications)
Abstract Quantitative understanding of ion transport mechanism is crucial for numerous applications of two-dimensional (2D) nanochannels, but is far from being resolved. Here, we formulated a theoretical framework for both self-diffusion and electromigration of hydrated monatomic ions in various 2D nanochannels (e.g. graphene, h-BN, g-C3N4, MoS2), by molecular dynamics simulations. The self-diffusivity and mobility of ions in 2D nanochannels both increases linearly with ion-wall distance for small hydrated ions, yet keeps constant for large ones. The underlying mechanism reveals that when ions approach water-layers in nanochannels or possess large hydration shell, their hydration shells become severely distorted. This increases the free energy difference between hydration shell and the surrounding water-layers, water residence time in hydration shell and ion-water friction. Several involving quantitative relations were revealed, with Nernst–Einstein relation validated with both simulations and theoretical derivation. This work shows profound implications for various applications, including ion-sieving, nanodevices and nano-power generators, etc.